KAPASITAS ULTIMIT DAN KAPASITAS GESER BALOK BETON BERTULANG MUTU TINGGI BERAGREGAT BATU PUTIH - Laksmi Irianti (UNIVERSITAS LAMPUNG, 2010)
Limitation of concrete constituent’s reserve, especially coarse aggregate cause need coarseaggregate taken from others region, so that it will increase price and economy value the coarseaggregate. Therefore, several researches are done to get a cheap building material but satisfyrequirements. Purposes of the research are to know flexural strength and shear strength of highstrength reinforced concrete beam that uses white stone with compression strength of 50 Mpa.White stones are taken from hill around Bandar Lampung used to replace coarse aggregate arecommonly used as concrete coarse aggregate in concrete. Sample of the research consist of threecylinders concrete (d = 150 mm and h = 300 mm) for compressive strength test concrete, 3concrete beams (b = 100 mm, h = 100 mm and L = 300 mm) for concrete flexural strength test 3beams double L for shear strength test concrete, 3 reinforced concrete beams (b = 120 mm, h =185 mm and l = 1350 mm) for beam bent strong test and 3 reinforced concrete beams (b = 120mm, h = 200 mm and L = 800 mm) for shear strength test beam. This watchfulness test thingconsists of: 3 concrete cylinders (d = 150 mm and h = 300 mm) for compressive strength testconcrete, 3 concrete beams (b = 100 mm, h = 100 mm and l = 300 mm) for concrete flexuralstrength test, 3 beams double L for shear strength test concrete, 3 reinforced concrete beams (b= 120 mm, h = 185 mm and l = 1350 mm) for beam bent strong test and 3 reinforced concretebeams (b = 120 mm, h = 200 mm and l = 800 mm) for shear strength test beam. From beamflexural testing result that have been done, that white stone use as concrete aggregate in Highstrength reinforced concrete beam gave ultimate capacity of 12,375.106 Nmm or 4,3603 % higherthan nominal ultimate capacity (beam nominal capacity). Therefore, white stone can be used asconcrete coarse aggregate in reinforced concrete beam element. From shear testing result hasbeen done, it can be seen that shear strength obtain from testing are slightly different from shearstrength predictions referrer to SK SNI T-15-1991-03, ACI 318-83 M and zsutty equation; thedifferences are only 0,7 % - 28,9 %. Therefore, white stone can be used as concrete coarseaggregate in reinforced concrete beam structure element.